2023
DOI: 10.1002/cctc.202301125
|View full text |Cite
|
Sign up to set email alerts
|

Indium‐based Catalysts for CO2 Hydrogenation to Methanol: Key Aspects for Catalytic Performance

Anne Wesner,
Philipp Kampe,
Nick Herrmann
et al.

Abstract: CO2 hydrogenation utilizing sustainably produced hydrogen and CO2 derived from industrial exhaust gas represents a pivotal technology for chemical energy storage and climate change mitigation. This work aimed to identify the best combination of catalyst support, synthesis method and promotor for In2O3/ZrO2 catalysts in a typical fixed‑bed configuration. Intense characterization using ICP‐OES, XRD, XPS, N2‐physisorption, CO2‐TPD, H2‐TPR and SEM‐EDX provide molecular insights into the different effects caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…An increase of catalyst surface area (80.66 m 2 ·g –1 ) by Ni doping was observed as well, leading to a better accessibility of the reactants. No methanation was observed, which is well in line with the literature. ,, After 90 h time on stream, the active productivity at the reactor outlet increased slightly from 2.96 g MeOH ·g In+Ni –1 ·h –1 to 3.07 g MeOH ·g In+Ni –1 ·h –1 with no apparent deactivation. Besides nickel, other promoter metals such as copper and cerium have been tested as well (Table ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…An increase of catalyst surface area (80.66 m 2 ·g –1 ) by Ni doping was observed as well, leading to a better accessibility of the reactants. No methanation was observed, which is well in line with the literature. ,, After 90 h time on stream, the active productivity at the reactor outlet increased slightly from 2.96 g MeOH ·g In+Ni –1 ·h –1 to 3.07 g MeOH ·g In+Ni –1 ·h –1 with no apparent deactivation. Besides nickel, other promoter metals such as copper and cerium have been tested as well (Table ).…”
Section: Resultssupporting
confidence: 91%
“…Building on the work of Frei et al and Kampe et al, ,, it was shown that nickel-promoted In 2 O 3 /ZrO 2 could enhance the catalytic performance compared to pure In 2 O 3 /ZrO 2 . To determine the spatially resolved difference in catalytic performance, we tested the Ni–In 2 O 3 /ZrO 2 catalyst in the CPR at the same reaction conditions ( p = 50 bar, T = 250 °C, see Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This was due to the stronger desorption ability of Ni for H 2 compared to that of Cu. 41 Combining this with findings from the literature, H 2 spilled over from Ni to Cu, [42][43][44] thereby providing more desorbed H 2 , which further contributed to the increase in hydrogenation ability.…”
Section: Resultssupporting
confidence: 59%
“…These values are in good agreement with those reported elsewhere. [58][59][60] Further characterisation of the materials with N 2 -physisorption shows that the catalyst surface, pore volume and average pore diameter decrease with increasing indium content (see Fig. S6 in the ESI †).…”
Section: Catalyst Compositionvariation Of Indium Contentmentioning
confidence: 99%